Contact line dynamics of two-dimensional evaporating drops on heated surfaces with temperature-dependent wettabilities. (January 2019) - Ye, Xuemin; Zhang, Xiangshan; Li, Minglan; Li, Chunxi; Dong, Shuai
Highlights: Dynamics of contact line of an evaporating drop on a uniformly heated substrate is examined. Contact line motion is controlled by the wettability of the substrate. Contact line pinning and partial pinning are realised by changing sensitivity coefficients. Contact line motion is effectively manipulated by sensitivity coefficient of solid-gas interface theoretically. Abstract: The dynamics of the evaporation of a sessile drop on a uniformly heated, horizontal, solid substrate is considered. Based on the lubrication theory and Navier slip condition, an evolution equation for the drop height of the two-dimensional drop is established. The effects of evaporation and the dependence of liquid–solid, solid–gas, and liquid–gas surface tensions on temperature are analysed. The present model indicates that the drop evolution is governed by capillary force, gravity, thermocapillary force, and evaporation. Numerical results show that gravity exerts a promoting effect on drop spreading, while capillary force and thermocapillary force inhibit drop spreading. The typical features, including contact line pinning, partial pinning, and depinning modes during drop evaporation, are illustrated by changing temperature sensitivity coefficients in the present model. The contact line motion is controlled by the wettability of the substrate and the temperature sensitivity coefficient of the solid–gas interface has a great influence on contact line dynamics. It is effective to manipulate the contact line during the volatile drop movement by regulating the temperature sensitivity coefficient of the solid–gas interface theoretically. However, the realisation of manipulation is highly dependent on the development of measurement techniques.